1999
DOI: 10.1002/(sici)1521-3803(19991201)43:6<385::aid-food385>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Properties of some citrus seeds. Part 3. Evaluation as a new source of protein and oil

Abstract: The chemical composition and minerals content of citrus seeds and its flours, the characteristics and structure of citrus seed oils as well as nutritional properties were studied. The citrus seeds and its flours were rich in oil and protein, respectively. Both citrus seeds and flours proved to be a good source for minerals K, Ca, P, Na, Fe and Mg. The flours of citrus seeds were rich in leucine, valine, total aromatic and total sulfur amino acids compared to FAO/WHO reference. Refractive index, specific gravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 23 publications
1
16
2
Order By: Relevance
“…The high oil content makes the seed material interesting for the production of oil. The fatty acid composition of some Citrus seed oils has been identified by Saidani et al, 2004;El-Adawy et al, 1999;AbdelRahaman et al, 1980;Lazos and Servos, 1988;habib et al, 1986. Previous studies on some Rutaceae seed oils have been reported by several authors (henderson and Kesterson, 1963;Abdel-Rahaman, 1980;habib et al, 1986;Lazos and Servos, 1988;Trandjiiska and Nguyen, 1989;helmy, 1990;Ajewole and Adeyeye, 1993;hassanein, 1999). Limited studies on the occurrence and variability of have been conducted (Abdel-Rahaman, 1980;habib et al, 1986;Lazos and Servos, 1988;Trandjiiska and Nguyen, 1989;Saidani et al, 2004;Reda et al, 2005).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The high oil content makes the seed material interesting for the production of oil. The fatty acid composition of some Citrus seed oils has been identified by Saidani et al, 2004;El-Adawy et al, 1999;AbdelRahaman et al, 1980;Lazos and Servos, 1988;habib et al, 1986. Previous studies on some Rutaceae seed oils have been reported by several authors (henderson and Kesterson, 1963;Abdel-Rahaman, 1980;habib et al, 1986;Lazos and Servos, 1988;Trandjiiska and Nguyen, 1989;helmy, 1990;Ajewole and Adeyeye, 1993;hassanein, 1999). Limited studies on the occurrence and variability of have been conducted (Abdel-Rahaman, 1980;habib et al, 1986;Lazos and Servos, 1988;Trandjiiska and Nguyen, 1989;Saidani et al, 2004;Reda et al, 2005).…”
Section: Discussioncontrasting
confidence: 72%
“…Two of the main constituents of Citrus seeds are seed meal, consisting of protein and seed oil. Citrus seeds contain about 36% oil and 14% protein (Braverman, 1949;El-Adawy et al, 1999). The high oil content makes the seed material interesting for the production of oil.…”
Section: Discussionmentioning
confidence: 91%
“…Citrus seeds contain from 26 to 42% of oil and are a good source of K, Ca, Na, Fe and Mg (El-Adawy et al, 1999). Saïdani et al (2004) verified that oils extracted from Tunisian citrus seeds are mostly constituted of triacylglycerols that are rich in unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Wastes from industrial processing are composed of peels, seeds and pulps representing 45 to 58% of the raw processed fruit (El-Adawy et al, 1999).…”
mentioning
confidence: 99%
“…As for Perario seed oil obtained more linoleic acid, with 31.86%. This value is lower than that reported by El-Adawy et al (1999) (38.4%) for orange seed oil.…”
Section: Resultsmentioning
confidence: 71%